The Fourth Plan Mid-Term Appraisal Volume II - Planning Commission (Planning Commission, 1971)
The Plan has set two objectives namely, to provide the conditions necessary for a sustained increase in agricultural production of about 5 per cent per annum over the next decade and to enable as large a section of the rural population as possible, including the small cultivator, the farmer in dry areas and the agricultural labourer to participate in development and share its benefits.
Government of India, Planning Commission